Post‐harvest conservation practices, related insect pests of stored pearl millet (Pennisetum glaucum (L) R. Br.), and their management in northern Benin - Alagbe, T.O.; Loko, Y.; Djegbe, I.; Gandjala, J.; Gavoedo, D.M.; Tamo, M. (2025)
Background Pearl millet (Pennisetum glaucum (L.) R. Br.) production has decreased over the years due to several constraints, including insect pest attacks, which contribute to its status as neglected and underutilized species in Benin. In order to develop an integrated pest management strategy, we documented farmers’ post-harvest conservation practices, perceptions, and management of storage insect pests. Four hundred millet producers were surveyed using a semi-structured questionnaire in 76 villages in northern Benin. The entomofauna associated with stored pearl millet was identified by extracting samples from farmers’ storage structures and incubating them for a month in the laboratory. Results Our results showed that farmers perceived insect pests as the most important constraint to pearl millet storage. Vernacular taxonomy and local nomenclature of insect pests of stored pearl millet varied among sociolinguistic groups. Four species of insects were associated with stored millet with the weevils Sitophilus oryzae L. and Sitophilus zeamais L. as the most important ones. Three storage structures (attic, bedroom, and store) and a storage tool (polypropylene bags) were inventoried. Synthetic chemical insecticides were the most commonly used method for protecting stored millet. Also, farmers employed four plants that repel and kill insects to safeguard stored pearl millet. A differential sensitivity of pearl millet varieties to storage insect attacks was reported with four potential resistant varieties. Some factors that influence the use of a pest management method were determined. Conclusions The development of an integrated pest management needs to test the sensitivity of resistant varieties and the bioactivity of recorded insecticidal plants. The farmers’ perception suggests that the Souhoun n’nin gberenou landrace and the usage of bark of A. senegalensis and leaves of A. indica are the best ways to preserve millet for a long time. Raising awareness among pearl millet producers on good storage practices and the biological management of storage insect pests were recommended. Factors that influence the use of pest management methods must be integrated into the development of national strategies.